Lipid Nanoparticles as Carriers for Bioactive Delivery - Dhiman, Neerupma; Awasthi, Rajendra; Sharma, Bhupesh; Kharkwal, Harsha; Kulkarni, Giriraj T. (Frontiers in Chemistry, 2021)
Nanotechnology has made a great impact on various industries including pharmaceutical, biotechnology, food and cosmetics industries. It is a well-known fact that more than 40% of the approved drugs are lipophilic in nature and have solubility issues which influence the release profile and bioavailability of drug molecules. Therefore, numerous approaches have been reported to administer the lipophilic drugs with improved solubility and bioavailability. Nanotechnology plays a crucial role in targeted drug delivery of poorly soluble drugs. Nanotechnology based drug delivery systems can be classified as solid lipid nanoparticulate drug delivery systems, emulsion-based nano-drug delivery systems, vesicular drug delivery systems, etc. Nanotechnology presents a new frontier in research and development to conquer the limitations coupled with the conventional drug delivery systems through the formation of specific functionalized particles. This review presents a bird’s eye view on various aspects of lipid nanoparticle as carriers for bioactive molecules i.e. synthesis, characterisation, advantage, disadvantage, toxicity and application in medical field. Updates on recent development in terms of patents and clinical trials of the SLNs and NLCs has also been discussed in this article.